The Late Glacial-Early Glaciomarine Transition in the Ottawa Valley: Evidence for a Glacial Lake? - Naldrett, Dana (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTRhythmites overlying either cross-bedded sand or diamicton are found throughout the Ottawa Valley. Previously thought to be restricted glacial lake sediments, they are now known to be widespread, and represent a large proglacial lake which preceded the Champlain Sea. The rhythmites consist of thin silt and clay laminae which fine upwards and contain slump, flame, shear (ice-contact?) and fluid escape structures. Ice-rafted material is common. The ostracode Candona cf. C. subtriangulata occurs in low numbers and indicates a freshwater body with depth of approximately 200 m. The alternation of silt and clay rhythmite laminae is characteristic of deposition by underflow and overflow currents, respectively. To produce underflows with typical glacial outwash concentrations may require discharge into fresh rather than marine water. This evidence and the widespread occurrence of rhythmites throughout the Ottawa Valley and the Rideau Lakes area suggests a large proglacial lake as the sedimentary basin. The lake is tentatively correlated with the Belleville Phase of Glacial Lake Iroquois and the Ft. Ann Phase of Glacial Lake Vermont. These phases occurred at depths consistent with the requirements for Candona survival. The water body which existed in the Ottawa area is here called Lake Rideau after the type locality where rhythmites were first observed. Generation of such a lake favours the more conventional "window blind" model for déglaciation rather than the calving bay concept.